Gender Differences in Outpatient Pediatric Drug Utilization: A Cohort Study From Southern Italy - Ferrajolo, Carmen; Sultana, Janet; Ientile, Valentina; Scavone, Cristina; Scondotto, Giulia; Tari, Michele; Trifirò, Gianluca; Rossi, Francesco; Capuano, Annalisa (Frontiers in Pharmacology, 2019)
Objective The aim of this retrospective population-based cohort study is to in-depth investigate gender-specific drug utilization pattern in pediatric outpatient population. Methods By using a large administrative database of the Local Health Unit of Caserta (Southern Italy), a pediatric cohort from the birth to 18 years has been observed over six years (from 1st January 2010 to 31st December 2015). Yearly prevalence of drug use per 100 inhabitants as well as the median number of prescriptions was stratifying by gender. Prevalence of acute and recurrent use of the most frequently used active substances has been calculated for the year 2015. Results A decreasing trend of prevalence of drug use (by 3.2%, with a reduction of median prescription number) was observed in children for both sexes, from 2010 to 2015. In 2015, the drug classes most commonly used among children of any age were modestly but consistently prescribed more to males than to females: systemic anti-infective drugs (M=43.5%; F=42.3%), respiratory tract drugs (M=29.0%; F=26.1%), and hormones (M=13.1%; F=11.3%). Irrespective to the gender, beclomethasone was the most utilized active substance in the first two years of life, while thereafter amoxicillin/clavulanate in combination. Conclusions In a large scale of pediatric outpatients no major difference was seen between genders, although commonly used drug classes, in particular, antibiotics, respiratory tract drugs and hormones are prescribed modestly but consistently more to males than to females. Our utilization data can support research exercises on specific medicine that could have a large impact on pediatric population.